The Development of Principle of Activity - Valatkienė, Stasė (Acta Paedagogica Vilnensia, 1999)
The article presents historical development of principle of activity from the primitive culture education till our days. Author gives the main attention to antique education, education of the Middle Ages, classical pedagogy. The new pedagogical trends are emphasized especially. The article also shows the development of principle of activity in Lithuania and the connection between the “new education” and Lithuania.
Keywords: history of education; Principle of Activity; classical pedagogy; pedagogical trends; “new education”